Meningkatkan Kemampuan Membaca Melalui Media Kartu Kata Pada Anak Usia Dini - Nur aini Nur aini; Muhammad Yusri Bachtiar; Indrawati Indrawati (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study generally aims to improve children's language skills in reading through word cards in group B at Tunas Harapan Kindergarten, Wringin District, Bondowosos Regency. The method applied in this research is the Classroom Action Research approach. (CAR) with the subject of group B totaling 20 children. Data analysis technique by holding two limited face-to-face meetings. This Classroom Action Research shows an increase in early childhood reading skills through the make a match method with word card media. This is evidenced by the results of the achievement of student development has increased; at the first meeting the achievement of student development was 52% and at the second meeting was 87%. Thus, it can be concluded that the use of word card media can improve children's ability to read in Tunas Harapan Kindergarten, Wringin District, Bondowoso Regency.